Energy efficiency and CO2 emissions in Swedish manufacturing industries (2012)
This paper analyses the trends in energy consumption and CO2 emissions as a result of energy efficiency improvements in Swedish manufacturing industries between 1993 and 2008. Using data at the two-digit level, the performance of this sector is studied in terms of CO2 emissions, energy consumption, energy efficiency measured as energy intensity, value of production, fuel sources, energy prices and energy taxes. It was found that energy consumption, energy intensity and CO2 emission intensity, measured as production values, have decreased significantly in the Swedish manufacturing industries during the period studied. The results of the decomposition analysis show that output growth has not required higher energy consumption, leading to a reduction in both energy and CO2 emission intensities. The role of structural changes has been minor, and the trends of energy efficiency and CO2 emissions have been similar during the sample period. A stochastic frontier model was used to determine possible factors that may have influenced these trends. The results demonstrate that high energy prices, energy taxes, investments and electricity consumption have influenced the reduction of energy and CO2 emission intensities, indicating that Sweden has applied an adequate and effective energy policy. The study confirms that it is possible to achieve economic growth and sustainable development whilst also reducing the pressure on resources and energy consumption and promoting the shift towards a low-carbon economy.